Internationalization of higher education: challenges, strategies, policies and programs - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Zolfaghari, Ali (David Publishing Company, 2009)
In today’s changing world, the idea of internationalization of higher education especially in developing countries has been deduced from globalization of education process. The international aspect of higher education is becoming increasingly important, composite, and confusing. The higher education has an effect on the society through policy-making, funding, and planning. The purpose of this paper is to analyze the meaning, definition, importance, necessity, and pre-requisites of internationalization of higher education. This paper also studies the programs and strategies of internationalization of higher education. Key challenges for the future direction of internationalization are identified in this paper.